Penyuluhan Pembibitan Ikan Patin (Pangasius hypopthalmus) Skala Mikro di Kelurahan Sialang Sakti, Pekanbaru, Riau - Sari, Vebrita; Ayu, Febri; Aulia, Muharani (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
In the Sialang Sakti Village, Pekanbaru City, there is a group of women that used to conduct a household scale fish culture activities specifically catfish nursery (Pangasius hypopthalmus). Most of them using a simple earthen pond. They did not apply any modern technique in culturing the fish. To improve the ability of the women community in culturing fish, a dissemination of environmental friendly fish culture technique was conducted specifically catfish nursery. Slides and a simple manual book for catfish nursery in fish culture was used during the training. The community were also trained to construct tarp ponds, feeding, rearing and managing the water quality in the pond. Twenty five women that were belonged to “PKK” group attended the training. Before the training, their knowledge on fish nursery was very low, but after the training, their knowledge improved by 85%. Results of monitoring and evaluation activities shown that the women from the PKK group were able to catfish nursery with simple earthen pond and sustainable.